(untitled) (Fiep Bulletin - online, 2013)
There are twenty-two island countries and territories in Oceania dispersed over 30 million km of the Pacific Ocean. Eight million people live in the Pacific. The broad ethnic groups are Melanesian, Polynesian and Micronesian. New Zealand and Australia have strong connections with most Pacific countries due to migration, travel, trade, and strong political links. Many of the developing states are characterised by geographical isolation not only within their territory but also from other pacific states. In addition limited resources to promote economic growth, problems with the government infrastructure, to ensure that effective delivery of education and health services are in place, compound the difficulties. The developing tourism industry especially in Samoa, Fiji and the Cook islands is helping to improve the economic stability of these states. (1) Undoubtedly the two developed nations: Australia (22.7 million people) and New Zealand (4.4 Million) have an influence on supporting the economies and education in the developed territories.